Farm - Chancellor Press (Chancellor Press London, 2013)
Farm," published by Octopus Publishing Group in 2013. This 24-page paperback is part of the "What Can I See?" series, designed to encourage observational skills and vocabulary development in young readers. The book invites children to explore the vibrant world of the farm, identifying various familiar and less familiar objects, from cows and cockerels to ducks and donkeys. Each discovery is accompanied by fascinating facts, making the learning experience both fun and informative.